Bioresponsive carbon nano-gated multifunctional mesoporous silica for cancer theranostics - Prasad, Rajendra; Aiyer, Sandhya; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Nanoscale, 2016)
Designing bioresponsive nanocarriers for controlled and efficient intracellular drug release for cancer therapy is a major thrust area in nanomedicine. With recent recognition by the US FDA as a safe material for human trials, mesoporous silica nanoparticles (MSNPs) are being extensively explored as promising theranostic agents. Green fluorescent carbon quantum dots (CQDs), though known as possible alternatives for their more toxic and relatively less efficient predecessors, are less known as gate keepers for drug release control. We report for the first time an efficient bioresponse of CQDs when judiciously designed using glutathione cleavable (redox responsive) disulphide bonds. When the anticancer drug doxorubicin loaded MSNPs are capped with these CQDs, they display promising drug release control on exposure to a mimicked intracellular cancer environment. Their dual functionality is well established with good control on preventing the premature release and exceptional bio-imaging of HeLa cancer cells. Fluorescence images prove selective targeting of HeLa cells by overexpression of folate receptors from the surface functionalised folic acid ligand. Extensive characterisation using XRD, TEM, BET analysis, drug loading tests, drug release kinetics, MTT assay and fluoroscence cell imaging helps in understanding the multi-functionalities of the successful design, extending its scope with exciting prospects towards non-invasive targeted drug delivery and bio-imaging for effective cancer diagnosis and treatment.